Analysing the Reading Preferences and Degree of Reading Enjoyment of B Ed Students - Suryavanshi, Dr Meena S (Journal of Advanced Research in Library and Information Science, 2025)
Reading fosters the development of intellectual abilities such as vocabulary, comprehension, critical thinking, and problem-solving techniques. Establishing a reading culture or habit is essential for promoting academic, intellectual, and personal development as well as lifelong learning. Children who read a lot can do better academically because it helps them build strong writing and reading comprehension abilities as well as a comprehensive understanding of many different areas. Investigating the reading choices and habits of student teachers enrolled in their second year of a bachelor’s degree in education is the goal of this study. Technology has the potential to foster a culture of reading as well. The study’s participants still have solid reading habits and a favourable attitude toward reading activities despite the advancement of media, technology, and other things that affect their preferences and reading habits.